A SWOT ANALYSIS OF ONLINE ROOM RESERVATION IN HOTEL SECTORS. (A CASE STUDY IN BALI HSOVEREIGN HOTEL) - Sanjaya, I Wayan Kiki; Arianty, A.A. Ayu Suwi; Suwintari, I Gusti Ayu Eka; Dewi, I Gusti Ayu Melistyari (Institut Pariwisata dan Bisnis Internasional, 2020)
The present study discusses a SWOT analysis of online reservation applied in HSovereign Hotel, Tuban, Bali. The hotel expects to obtain the easier and faster services in room reservation in hotel sectors by using internet media through online process (e-commerce). However, there are several challenges occur in practice as seen in HSovereign Hotel. As a result, the quality of thereservationservices is considered bad, not professional, and ultimately gives impact upon consumers’ satisfaction. Therefore, the problem that will be observed in the present study is how the advantages, disadvantages, opportunities and threats of e-commerce usage in HSovereign Hotel can be identified. A descriptive-qualitative research is the type of the present study. The data of the present studywere obtained from observation, interview, and documentation in order to find out the advantages, disadvantages, opportunities and threats of online reservation in H Sovereign Hotel. Furthermore, the theories used in the present study are: hotel, reservation, room online reservation, definition of e-commerce, and room occupancy rate. The data were presented in both analytical descriptive and narrative, and also supported by presenting tables, maps, and figures. Based on the result of analysis, the advantages of e-commerce usage in online reservation services which attracted more residents to come is the effectiveness of online reservation system in H Sovereign Hotel. On contrary, the disadvantages of online reservation relies on its dependency oninternet connection and server system in H Sovereign Hotel. The opportunity can be identified from using online reservation is it could be a media promotion which enables consumers to reserve in the last minute, and the threats found are cancellations ensue and fake bookings that extremely threaten information system of room reservation in H Sovereign Hotel.